Human Wharton’s Jelly-Derived Mesenchymal Stem Cells Promote Corneal Epithelial Growth On Polyhydroxyalkanoate For Corneal Regeneration - Mohamed, Mohamed Salih Elnour (2022)
Corneal transplantation has limitations such as graft rejection, disease transmission, and scarcity of tissue supply. Tissue engineering and regenerative medicine technology for future corneal diseases treatment strategies involve the use of safe, commonly available, biocompatible, and biodegradable polymer, together with the biologically active molecules and stem cells. Polyhydroxyalkanoate (PHA) was biosynthesized and characterized by testing the monomer composition and water contact angle. In vitro degradation was explored using lipase enzyme.